2016
DOI: 10.1007/s12035-015-9642-z
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Promotes Microglia Activation Through Beclin-1-Atg5 Pathway in Intracerebral Hemorrhage

Abstract: Previous study demonstrates that intracerebral hemorrhage (ICH) promotes microglia activation and inflammation. However, the exact mechanism of microglia activation induced by ICH is not clear. In this experiment, microglia autophagy was examined using electron microscopy, conversion of light chain 3(LC3), and monodansylcadaverine (MDC) staining to detect autophagic vacuoles. We found that ICH induced microglia autophagy and activation. The suppression of autophagy using either pharmacologic inhibitors (3-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Reduced microglia activation is accompanied by reduced levels of proinflammatory cytokines and chemokines and increased levels of anti-inflammatory cytokines, and this might account for the reduced neural stem and progenitor cell death in neuronal Atg7 KO mouse pups or vice versa . Autophagy has important roles in the regulation of microglia activation and inflammation, 44, 45 and the interaction between autophagy and microglia activation needs to be investigated further. 45, 46 …”
Section: Discussionmentioning
confidence: 99%
“…Reduced microglia activation is accompanied by reduced levels of proinflammatory cytokines and chemokines and increased levels of anti-inflammatory cytokines, and this might account for the reduced neural stem and progenitor cell death in neuronal Atg7 KO mouse pups or vice versa . Autophagy has important roles in the regulation of microglia activation and inflammation, 44, 45 and the interaction between autophagy and microglia activation needs to be investigated further. 45, 46 …”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is another contributing factor to the secondary injury after ICH. Research indicated that many substances could activate autophagy which caused secondary injury in the brain after ICH [5153]. We are glad to see that the suppressed autophagy effect of artesunate has been confirmed in in vitro experiment [54].…”
Section: Effect Of Artesunate On Central Nervous System Diseasesmentioning
confidence: 96%
“…The incidences of ICH bring damage to the brain function, results in cognitive decline or brain injury 4 . The previous experiments have indicated that microglia mediated inflammation contributed to the pathology progress of ICH 5 7 .…”
Section: Introductionmentioning
confidence: 96%